Soil physical quality of Mollisols quantified by a global index - Pablo Javier Ghiberto; Silvia Imhoff; Paulo Leonel Libardi; Álvaro Pires da Silva; Cassio Antonio Tormena; Miguel Ángel Pilatti (Scientia Agricola, 2015)
Indicators synthesizing the state of the structural quality and the function of the porous system are useful for assessing soil production capacity as well as the way it may serve natural ecosystems. This research aimed (i) to determine indicators of the state and function of the porous system, (ii) to use them to derive a global index to characterize the soil physical quality, and iii) to establish a reference pore-size distribution curve for Mollisols from the province of Santa Fe (Argentina). Sixty water retention curves (WRC) of A and B horizons of Mollisols, with clay varying between 119 and 538 g kg−1, organic matter between 5 and 40 g kg−1, and soil bulk density between 1.09 and 1.49 Mg m−3, were used. The indicators measured were: pore size distribution, macroporosity (PORp), air capacity (ACt) and plant-available water capacity (PAWC) among others. Soils were classified into four groups according to their physical properties and a reference WRC was determined. From this WRC and considering a total porosity of 0.514 m3 m−3, PORp was 0.035 m3 m−3, ACt 0.153 m3 m−3, field capacity 0.361 m3 m−3, permanent wilting point 0.136 m3 m−3 and PAWC 0.225 m3 m−3. Both the high silt content and low organic matter content confer on the soil characteristics with low stability, excess of small pores and low porosity of the macropore domain. Consequently, the capacity to quickly drain the water excess and allow root proliferation was not optimal, possibly due to the high silt or clay content and the low sand content, characteristic of the soil matrix of these Mollisols.